Principled moral reasoning: Is it a viable approach to promote ethical integrity? - Weber, James (Journal of business ethics, 1991)
In response to recent recommendations for the teaching of principled moral reasoning in business school curricula, this paper assesses the viability of such an approach. The results indicate that, while business students' level of moral reasoning in this sample are like most 18- to 21-year-olds, they may be incapable of grasping the concepts embodied in principled moral reasoning. Implications of these findings are discussed.